Assessment of cognitive dysfunction using the Montreal Cognitive Assessment test: rate, severity and comparison with the Clock test alone in a population of patients referred for TAVI. Issue 4 (29th December 2021) - Monnin, C; Besutti, M; Ecarnot, F; Guillon, B; Chatot, M; Chopard, R; Yahia, M; Meneveau, N; Schiele, F
Abstract: Background: Although not recommended in routine practice, the detection and quantification of Cognitive Dysfunction (CD) in older patients might have an impact on clinical decisions. We assessed the rate and severity of CD in an unselected population of patients referred for Transcatheter Aortic Valve Implantation (TAVI) using the Montreal Cognitive Assessment (MoCA) and using the Clock Drawing Test (ClockT) alone. Methods: The MoCA was performed before TAVI by an experienced operator. The ClockT was scored out of 10 points according to the Rouleau rating scale. CD was defined according to the MoCA score: No CD if score ≥26, mild CD if score 18–25, moderate if 10–17 and severe if <10. Inter-observer reliability of scoring on the ClockT was estimated with the Bland-Altman method. Agreement between MoCA scores and the ClockT for ruling out and for detecting CD were measured with the Kappa coefficient. Results: MoCA was performed in 83 consecutive patients referred for TAVI, median age 85 years. The mean time required for assessment was 11±2 min for the MoCA and 3±2 min for the ClockT. The mean MoCA score was 21±4.5: CD was excluded in 17 (20%) pts, mild CD was found in 50 (60%), moderate in 15 (18%) and severe in one (1%). The median ClockT score was 8 (interquartile 6; 9), with excellent inter-observer concordance (Kappa= 0.84). Overall, 51% of the variance of the MoCA score was explained by the ClockT alone according to multiple regression. A ClockT <7 detected a group with significantly lower MoCA score, compared to pts with higher ClockT scores (figure). Conclusion: Among patients referred for TAVI, CD can be excluded using the MoCA test in 20%, while moderate or severe CD is observed in 18%. The ClockT alone is faster to implement, reliable to interpret and enabled detection of patients with moderate CD when Rouleau scoring was <7. Funding Acknowledgement: Type of funding sources: None.